(untitled) (Scientific journal of the Fergana State University, 2024)
This article will focus on the Persian word “kharoson”, used by the poet in Alisher Navoi’s work “Saddi Alexandria”, about its belonging to the category of Ravish, about its role in the sentence, about morphological features. The scientific views of world and Uzbek linguists on adverbs are presented. In particular, the opinions of Uzbek and world linguists on the influence of the Persian-Tajik language on the Uzbek language were analyzed and the specific morphological features of the lexeme of one grammatical category were explained. In particular, the examples from the work show that the haroson lexeme is formed by adding an adverb to the noun haros, as well as the adverb –on, which can act as a noun, verb and adjective in a sentence.